A highly sensitive visual sensor for tetracycline in food samples by a double-signal response fluorescent nanohybrid. (February 2020) - Hu, Jing; Yang, Xiaofeng; Peng, Qianqian; Wang, Fengyi; Zhu, Yue; Hu, Xuan; Zheng, Baozhan; Du, Juan; Xiao, Dan
Abstract: In this study, a ratiometric fluorescent probe BCDs-Eu/CMP-cit was developed for the detection of tetracycline (TC) in food samples by simply mixing blue fluorescent carbon quantum dots (BCDs) and cytidine monophosphate (CMP)/europium coordination polymer nanoparticles (Eu/CMP-cit CPNs) together. In this ratiometric sensor, the emission of BCDs at 465 nm gradually decreased and that of Eu/CMP-cit CPNs at 620 nm significantly increased with the sequential addition of TC upon being excited at 380 nm, accompanyed by a remarkable fluorescence color change from bright blue to red. It was worth mentioning that both of the two components in BCDs-Eu/CMP-cit nanosystem were employed as response signals with different fluorescent signal output. Hence, the sensitivity to TC is greatly enhanced without being affected by other potentially interfering substances. Under the optimized conditions, a good linear relationship between the concentration of TC from 0.05 to 30 μM and the fluorescence intensity ratio of F 620 / F 465 was obtained. The detection limit was calculated to be 8 nM, which was much lower than that of most of the previously published methods. Moreover, this proposed nanosystem was also successfully applied to the assay of TC in food samples, including fish, lamb, beef, chicken, pork, egg, milk and honey, and the recovery rates were even comparable to those obtained from high performance liquid chromatography (HPLC)-based methods. Importantly, a paper-based visual sensor for TC in various food samples was devised by using filter paper embedded with BCDs-Eu/CMP-cit. The distinct fluorescent color changing from bright blue to red of the filter paper with different concentrations of TC demonstrated a great potential of as-prepared ratiometric fluorescent probe for the visual detection of TC in complicated real samples. Highlights: Sensitive ratiometric fluorescent probe for tetracycline detection was constructed. The probe was simple in design, rapid in response and cost-effective. The dramatic fluorescent color change displayed the high sensitivity of this probe. Paper-based visual sensor was successfully applied in real complex food samples.